Incomplete antenatal care despite high coverage: geographic and sociocultural barriers in Lao PDR - Kim, Hyunkyong; Han, Hyejung; Phommachan, Khammany; Yang, Yong Sook; Kim, Sung Hye (Frontiers in Public Health, 2025)
BackgroundDespite progress in maternal health in Lao PDR, timely access and the completeness of antenatal care (ANC) services remain uneven, particularly in remote provinces with high maternal mortality. Understanding the patterns of ANC utilization and barriers to receiving adequate care is essential to inform targeted interventions.ObjectiveThis study examined factors associated with early ANC initiation (≤12 weeks’ gestation), adequate ANC (≥4 visits), and the coverage of essential ANC components among women in two northern provinces.MethodsIn February 2023, we conducted a cross-sectional survey in Xiengkhuang and Huaphanh provinces, using stratified three-stage cluster sampling to recruit 380 women with children under 2 years. Face-to-face interviews collected data on ANC timing and frequency, receipt of 13 Ministry-of-Health-defined ANC services, and education on five key pregnancy danger signs. Descriptive statistics summarized utilization, and multivariable logistic regression identified predictors of timely and adequate ANC.ResultsWhile 95% of participants reported at least one ANC visit and 77.1% had four or more, only 34.5% began ANC within the first trimester. Lack of road access was associated with lower odds of timely and adequate ANC up to 59% (adjusted odds ratio [aOR] for adequate ANC: 0.41; 95% CI: 0.19–0.90). Ethnic minorities, specifically Hmong-Lu Mien women, were associated with 87% reduced odds of having adequate ANC e (aOR: 0.13; 95% CI: 0.02–0.71). Service completeness remained low: just 10.7% reported receiving all essential 13 ANC components, and comprehensive education on all five key pregnancy danger signs was rare (1.5%), and 1.5% reported receiving full education on danger signs; counseling on life-threatening symptoms reached 5.7%. Laboratory services (anemia screening 82.2%, HIV testing 78.4%) and iron supplementation (98%) were common, but only 24.4% reported folic acid provision.ConclusionDespite significant improvements in overall ANC coverage in Lao PDR, critical gaps persist in timely initiation and completeness of ANC services, particularly among geographically and ethnically marginalized groups. These findings underscore the urgent need for targeted interventions that address both geographic and cultural barriers and enhance the timeliness and completeness of ANC services to reduce disparities and maximize maternal health benefits in resource-limited settings.